Морфологічні особливості сечового міхура щурів в постнатальному періоді в нормі та після введення антигена - Хитрик, Аліна Йосипівна; Khitrik, A. Y. (Запорізький державний медичний університет, 2021)
В останні роки спостерігається невпинне зростання числа захворювань сечових шляхів у ранньому дитячому віці, особливе місце серед яких посідають гострий та хронічний цистит, багатофакторний характер формування яких включає як роль мікробного чинника, так і зниження бар’єрної функції сечових шляхів, їх місцевого специфічного та неспецифічного захисту, високий рівень пренатального антигенного навантаження. Тому з'ясування морфологічних особливостей сечового міхура, специфічних і неспецифічних факторів захисту його слизової оболонки в постнатальному онтогенезі при моделюванні стану збільшеного антенатального антигенного навантаження є необхідним для подальших досліджень та удосконалення методів діагностики та лікування захворювань сечової системи. In recent years, there has been a steady increase in the number of urinary tract diseases in early childhood, a special place among which have an acute and chronic cystitis, the multifactorial nature of the formation of which includes both the role of microbial factor and reduction of barrier function of the urinary tract, their local specific and nonspecific protection, high prenatal antigen load. Therefore, elucidation of morphological features of the bladder, specific and nonspecific factors of protection of its mucous membrane in early postnatal ontogenesis in modeling the state of increased antenatal antigen load is necessary for further research and improvement of methods for diagnosis and treatment of urinary tract diseases. Thesis paper is devoted to the study of morphological features of the bladder of rats in the postnatal period in normal condition and after intrauterine administration of staphylococcal toxoid. The study was performed on 192 Wistar rats, which were divided into 3 groups: intact, control and experimental. Depending on the observation period, the rats in each group were divided into 8 subgroups. 8 animals were studied in each subgroup. Histological, morphometric, electron microscopic, immunohistochemical, histochemical and statistical research methods were used
Morphological features of the bladder of rats in the postnatal period in normal condition and after antigen administration
Keywords: сечовий міхур; антигенна стимуляція; мікроциркуляторне русло; лімфоцити; bladder; antigenic stimulation; microvasculature; lymphocytes